Knockdown of Ran GTPase expression inhibits the proliferation and migration of breast cancer cells - Sheng, Chenyi (Mol Med Rep, 2018)
Breast cancer is the second leading cause of cancer-associated mortality in women worldwide. Strong evidence has suggested that Ran, which is a small GTP binding protein involved in the transport of RNA and protein across the nucleus, may be a key cellular protein involved in the metastatic progression of cancer. The present study investigated Ran gene expression in breast cancer tissue samples obtained from 140 patients who had undergone surgical resection for breast cancer. Western blot analysis of Ran in breast cancer tissues and paired adjacent normal tissues showed that expression of Ran was significantly increased in breast cancer tissues. Immunohistochemistry analyses conducted on formalin-fixed paraffin-embedded breast cancer tissue sections revealed that Ran expression was associated with tumor histological grade, nerve invasion and metastasis, vascular metastasis and Ki-67 expression (a marker of cell proliferation). Kaplan-Meier survival analysis showed that increased Ran expression in patients with breast cancer was positively associated with a poor survival prognosis. Furthermore, in vitro experiments demonstrated that highly migratory MDA-MB-231 cancer cells treated with Ran-si-RNA (si-Ran), which knocked down expression of Ran, exhibited decreased motility in trans-well migration and wound healing assays. Cell cycle analysis of Ran knocked down MDA-MB-231 cells implicated Ran in cell cycle arrest and the inhibition of proliferation. Furthermore, a starvation and re-feeding (CCK-8) assay was performed, which indicated that Ran regulated breast cancer cell proliferation. Taken together, the results provide strong in vitro evidence of the involvement of Ran in the progression of breast cancer and suggest that it could have high potential as a therapeutic target and/or marker of disease.